Pengaruh Kualitas Pelayanan Jasa Penyewaan Event Equipment Terhadap Kepuasan Pelanggan pada Cv. Bali Stage Expotama di Bali - Susila, Gusti Ayu Agung Ratih Prameswari; Sumadi, I Gede; Wirata, I Nengah (Journal of Event and Convention Management, 2024)
This study aims to analyze the effect of service quality on event equipment rental services at CV. Bali Stage Expotama on customer satisfaction. Quantitative method used in this research. Data was collected by distributing questionnaires to 38 consumers of CV Bali Stage Expotama and validity and reliability tests were carried out before the questionnaire was used to gather data. Data processing was carried out using the SPPS version 26 program and data analysis techniques using a simple linear regression test. Based on the results of data analysis, it is known that the service quality of event equipment rental services at CV. Bali Stage Expotama in Bali influences of customer satisfaction by 84.6%. The results of the analysis of service quality show that the tangible dimension gets a score of 3.89 (satisfied), the reliability dimension gets a score of 4.02 (satisfied), the responsiveness dimension gets a score of 4.06 (satisfied), the assurance dimension got a score of 3.99 (satisfied), the empathy dimension got a score of 3.97 (satisfied). These five dimensions get satisfied ratings, which means customers are satisfied with services of CV. Bali Stage Expotama and it is known that the tangible dimension gets the lowest rating.